Morfogênese e dinâmica do perfilhamento de tifton 85 sob irrigação e diferentes frequências de desfolhação - Severo, Paula de Oliveira (2020)
Changes on plant morphogenic characteristics modify sward structure and, consequently, alter microclimate wherein plants grown. In this sense, dynamics of pasture tiller population is altered, characterizing the complex and interdependent plant community nature and the flow of tissues in pasture ecosystem. The joint analysis of descriptive characteristics of morphogenesis and dynamics of grass tillers population, as well as identification of their relationships is relevant, because it allows understanding about patterns of plants response in environment, including grazing management and weather. These studies were carried out to evaluate Tifton 85 morphogenesis and tillering dynamics under irrigation and different defoliation frequencies. Initially, one experiment was conducted evaluating morphogenic and structural variables of Tifton 85 under different defoliation frequencies (121, 242, 363 and 726 degree-days (DD)), irrigation levels (irrigated and non-irrigated) and seasons (Spring, Summer and Autumn). Experimental design was sub-subdivided plots, irrigation levels being the main plots, defoliation frequencies sub-plots, and seasons the sub-subplots. In the second year, the Tifton 85 tillering dynamics under different defoliation frequencies (121, 242, 363 and 726 DD) and irrigation levels (irrigated and non-irrigated) were studied. Experimental design was subdivided plots, with irrigation levels as main plots and defoliation frequencies as sub-plots. Since there was no intense and lasting water restriction, effect of additional irrigation did not change Tifton 85 morphogenic and structural traits however some parameters of tillering dynamics were modified. When Tifton 85 was irrigated, lower rates of basal tillers mortality and higher axillary tillers survival rates were observed. Morphogenic variables Tifton 85, leaves only the expansion rates and stem have been modified in amplitude between cuts between 121 and 726 DD. Reduction of canopy height in these treatments and consequent improvement of luminous environment was not enough to increase rates of tiller appearance. Analyzing data of the two papers together and aiming to optimize production, perennial and structure of grazing canopy, the recommended cutting frequency is 242 DD, equivalent to 4 phyllochrons of Tifton 85.